2021
DOI: 10.1002/elps.202000371
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of endogenous and exogenous nucleic acids in “Touch DNA” components on hands

Abstract: Successful forensic DNA profiling from handled items is increasingly routine in casework. This "touch DNA" is thought to contain both cellular and acellular nucleic acid sources. However, there is little clarity on the origins or characteristics of this material. The cellular component consists of anucleate, terminally differentiated corneocytes (assumed to lack DNA), and the occasional nucleated cell. The acellular DNA source is fragmentary, presumably cell breakdown products. This study examines the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Other recent studies on DNA-TPPR include examining prevalence and persistence of DNA or saliva from car drivers and passengers [ [310] , [311] , [312] ], evaluation of DNA from regularly-used knives after a brief use by someone else [ 313 ], studying the accumulation of endogenous and exogenous DNA on hands [ 314 ] and non-self-DNA on the neck [ 315 ], considering the potential of DNA transfer via work gloves [ 316 , 317 ] or during lock picking [ 318 ], and investigating whether DNA can be recovered from illicit drug capsules [ 319 , 320 ] or packaging [ 321 ] to identify those individuals preparing or handling the drugs.…”
Section: Advancements In Current Practicesmentioning
confidence: 99%
“…Other recent studies on DNA-TPPR include examining prevalence and persistence of DNA or saliva from car drivers and passengers [ [310] , [311] , [312] ], evaluation of DNA from regularly-used knives after a brief use by someone else [ 313 ], studying the accumulation of endogenous and exogenous DNA on hands [ 314 ] and non-self-DNA on the neck [ 315 ], considering the potential of DNA transfer via work gloves [ 316 , 317 ] or during lock picking [ 318 ], and investigating whether DNA can be recovered from illicit drug capsules [ 319 , 320 ] or packaging [ 321 ] to identify those individuals preparing or handling the drugs.…”
Section: Advancements In Current Practicesmentioning
confidence: 99%
“…"Touch DNA" (tDNA) refers to the small amount of DNA transferred via skin cells to an object when it has been handled or touched [3,4]. Previous research has suggested that these deposits are a combination of nucleated cells (secreted through pores), anucleate corneocytes (from the outermost skin layer), and possibly fragmented cell debris [5][6][7][8]. In addition, DNA recovered from touched surfaces may contain cell-free nucleic acids (CNAs) that are also present in sweat [9].…”
Section: Introductionmentioning
confidence: 99%